2010
DOI: 10.1007/s12032-010-9764-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of pretreatment comorbidities in elderly patients with advanced non-small-cell lung cancer treated with chemotherapy or epidermal growth factor receptor-tyrosine kinase inhibitor

Abstract: A standard, valid assay of comorbidities for elderly patients with advanced non-small-cell lung cancer (NSCLC) who have received antitumor therapy is needed to provide useful prognostic information. The aim of this study was to analyze prognostic factors and validate classic Charlson comorbidity index (CCI) and comorbidity scores in elderly patients with advanced NSCLC treated with chemotherapy or epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs). A retrospective analysis was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Most observational studies have found that cancer patients with comorbidities have poorer survival than patients without comorbidities 411,24,2830. Cohort studies with 5–7 years of follow-up have reported 1.1- to 5.8-fold higher mortality for breast cancer patients with any comorbidity compared to patients with no comorbidity 4,20,26,31,32.…”
Section: Resultsmentioning
confidence: 99%
“…Most observational studies have found that cancer patients with comorbidities have poorer survival than patients without comorbidities 411,24,2830. Cohort studies with 5–7 years of follow-up have reported 1.1- to 5.8-fold higher mortality for breast cancer patients with any comorbidity compared to patients with no comorbidity 4,20,26,31,32.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Chen et al [ 24 ] (survival predictor—use of TKI) were similar to our study but may not be directly comparable as patients aged 70–79 years were excluded. On the contrary, the studies by Irisa et al [ 25 ] (survival predictor—histology subgroup, number of comorbidities, and CCI score) and Girones et al [ 26 ] (survival predictor—TMN staging) shared the same age cutoff of 70 years and overall study design. We have considered all the variables mentioned in these studies, but none was found to be a significant survival predictor; one possible explanation of this might be a sample bias as those with multiple comorbidities might not have been referred for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [ 24 ] found that in Chinese patients with advanced NSCLC aged 80 years or older, patients who received EGFR– TKI therapy had a significantly better prognosis (hazard ratio: 0.56), a benefit not found in chemotherapy or radiotherapy group. Irisa et al [ 25 ] found that NSCLC histology (HR 1.631), three or more comorbidities (HR 1.317), and a CCI of more than three (HR 1.321) were independent negative prognostic factors. Girones et al [ 26 ], however, found that TMN clinical staging (log-rank: p < 0.001), not CCI, was related to survival.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the usefulness of abbreviated instruments [32,37], such as the Cancer Aging Research Group and the Chemotherapy Risk Assessment Scale for High-age patients tools, is not definitively assessed. Despite this, the European Organization for Research and Treatment of Cancer Elderly Task Force and the International Society for Geriatric Oncology strongly recommend the application of CGA-based approaches in clinical practice [38].…”
Section: Clinical Evaluation Of Elderly Patients With Cancermentioning
confidence: 99%